2010
DOI: 10.4153/cjm-2009-054-5
|View full text |Cite
|
Sign up to set email alerts
|

Covering Maps and Periodic Functions on Higher Dimensional Sierpinski Gaskets

Abstract: Abstract. We construct covering maps from infinite blowups of the n-dimensional Sierpinski gasket SGn to certain compact fractafolds based on SGn. These maps are fractal analogs of the usual covering maps from the line to the circle. The construction extends work of the second author in the case n = 2, but a different method of proof is needed, which amounts to solving a Sudoku-type puzzle. We can use the covering maps to define the notion of periodic function on the blowups. We give a characterization of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Periodic and almost periodic functions on the infinite fractafold are considered, and a Fourier series description for the periodic functions is given, based on periodic eigenfunctions of the Laplacian (cf. also [46] for higher-dimensional examples). Let us remark that such coverings, as the ones considered in this paper, are not associated with groups of deck transformations.…”
Section: Introductionmentioning
confidence: 93%
“…Periodic and almost periodic functions on the infinite fractafold are considered, and a Fourier series description for the periodic functions is given, based on periodic eigenfunctions of the Laplacian (cf. also [46] for higher-dimensional examples). Let us remark that such coverings, as the ones considered in this paper, are not associated with groups of deck transformations.…”
Section: Introductionmentioning
confidence: 93%
“…It can be also used to define periodic functions on nested fractals. Such objects on the Sierpiński gasket and its higher dimension analogues were examined by Ruan and Strichartz [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…Strichartz [24]. Existing research on the infinite Sierpinski gasket and on other 'fractafolds' be found in [12,20,23,25,26,27]. In particular, we will use the important result concerning the spectrum of the Laplacian on the infinite Sierpinski gasket by A. Teplyaev [27].…”
Section: Introductionmentioning
confidence: 99%
“…Normalized solutions corresponding to p(cos 2t, ε), with ε = 0, 1, 2, 3, 4, 5, 6 in the left, and ε = 6, 7,8,9,10,20, 30, 40, 60, 80, 100, 160 in the right.…”
mentioning
confidence: 99%